Strategies to Extend Thrombolytic Time Window for Ischemic Stroke Treatment: An Unmet Clinical Need - Peña, Ike dela; Borlongan, Cesar; Shen, Guofang; Davis, Willie (Journal of stroke, 2017)
To date, reperfusion with tissue plasminogen activator (tPA) remains the gold standard treatment for ischemic stroke. However, when tPA is given beyond 4.5 hours of stroke onset, deleterious effects of the drug ensue, especially, hemorrhagic transformation (HT), which causes the most significant morbidity and mortality in stroke patients. An important clinical problem at hand is to develop strategies that will enhance the therapeutic time window for tPA therapy and reduce the adverse effects (especially HT) of delayed tPA treatment. We reviewed the pharmacological agents which reduced the risk of HT associated with delayed (beyond 4.5 hours post-stroke) tPA treatment in preclinical studies, which we classified into those that putatively preserve the blood-brain barrier (e.g., minocycline, cilostazol, fasudil, candesartan, and bryostatin) and/or enhance vascularization and protect the cerebrovasculature (e.g., coumarin derivate IMM-H004 and granulocyte colony-stimulating factor). Recently, other new therapeutic modalities (e.g., oxygen transporters) have been reported which improved delayed tPA-associated outcomes by acting through other mechanisms. While the above-mentioned interventions unequivocally reduced delayed tPA-induced HT in stroke models, the long-term efficacy of these drugs are not yet established. Further optimization is required to expedite their future clinical application. The findings from this review indicate the need to explore the most ideal adjunctive interventions that will not only reduce delayed tPA-induced HT, but also preserve neurovascular functions. While waiting for the next breakthrough drug in acute stroke treatment, it is equally important to allocate considerable effort to find approaches to address the limitations of the only FDA-approved stroke therapy.